Effects of metformin on acute respiratory distress syndrome in preclinical studies: a systematic review and meta-analysis - Wang, Liu; Tian, Yan-Fen; Deng, Wen-Qing (Frontiers in Pharmacology, 2023)
Introduction: in this study, we exerted a system review and meta-analysis to judge the effect of metformin on acute respiratory distress syndrome (ARDS) in a comprehensive and quantitative manner.Methods: we included studies that tested effects of metformin on ALI or ARDS in in vivo studies. We excluded literatures that data could not be extracted or obtained. Electronic search was conducted to retrieve relevant literatures from public databases, including pubmed, Web of Science, Embase, Scopus, and the Cochrane Central Register of Controlled Trials (inception to Jul 2023). Moreover, ProQuest Dissertations and Theses Global, Google scholar, and Baidu scholar were inquired. Retrieved literatures were screened and evaluated by pairs of reviewers independently according to pre-stated criteria. The SYstematic Review Center for Laboratory animal Experimentation (SYRCLE) risk of bias tool was used to evaluate methodological quality of eligible literatures. No restriction was exerted on publication status or language.Results: fifteen preclinical studies were analyzed in this meta-analysis. Pooled results showed metformin effectively decreased pulmonary wet to dry weight ratio (SMD = -2.67 (-3.53 to -1.81), I 2 = 56.6%), protein content (SMD = -3.74 (-6.76 to -0.72) , I 2 = 86.7%) and neutrophils (SMD = -3.47 (-4.69 to -2.26), I 2 = 0%) in BALF, pulmonary malondialdehyde (SMD = -1.98 (-3.77 to -0.20), I 2 = 74.2%) and myeloperoxidase activity (SMD = -3.15 (-4.79 to -1.52), I 2 = 74.5%), lung injury scores (SMD = -4.19 (-5.65 to -2.74), I 2 = 69.1%), and mortality at 24 h (RR = 0.43 (0.24 to 0.76), I 2 = 0%) 3 as well as 48 and 72h.Conclusions: metformin inhibited pulmonary inflammation and oxidative stress, and improved experimental lung injury and survival rate in animal models of ARDS.Results from randomized controlled trial are needed.